Answer: (3a + 2) • (4a2 - 2a + 9)
(no solution)
Step-by-step explanation:
Step by Step Solution
More Icon
STEP
1
:
Equation at the end of step 1
(3a + 2) • ((22a2 - 2a) + 9)
STEP
2
:
Trying to factor by splitting the middle term
2.1 Factoring 4a2-2a+9
The first term is, 4a2 its coefficient is 4 .
The middle term is, -2a its coefficient is -2 .
The last term, "the constant", is +9
Step-1 : Multiply the coefficient of the first term by the constant 4 • 9 = 36
Step-2 : Find two factors of 36 whose sum equals the coefficient of the middle term, which is -2 .
-36 + -1 = -37
-18 + -2 = -20
-12 + -3 = -15
-9 + -4 = -13
-6 + -6 = -12
-4 + -9 = -13
For tidiness, printing of 12 lines which failed to find two such factors, was suppressed
Observation : No two such factors can be found !!
Conclusion : Trinomial can not be factored
Final result :
(3a + 2) • (4a2 - 2a + 9)